Benefit of Physiologically Variable Over Pressure-Controlled Ventilation in a Model of Chronic Obstructive Pulmonary Disease: A Randomized Study - Dos Santos Rocha, Andre; Südy, Roberta; Bizzotto, Davide; Kassai, Miklos; Carvalho, Tania; Dellacà, Raffaele L.; Peták, Ferenc; Habre, Walid (Frontiers in Physiology, 2021)
Introduction: The advantages of physiologically variable ventilation based on a spontaneous breathing pattern have been demonstrated in several respiratory conditions. However, its potential benefits in chronic obstructive pulmonary disease have not yet been characterized. We used an experimental model of chronic obstructive pulmonary disease to compare respiratory function outcomes after 6 hours of physiologically variable ventilation versus conventional pressure-controlled ventilation. Materials and Methods: Rabbits received nebulized elastase and lipopolysaccharide throughout 4 weeks. After 30 days, animals were anesthetized, tracheotomized and randomized to receive 6 hours of physiologically variable (n=8) or conventional pressure-controlled ventilation (n=7). Blood gases, respiratory mechanics and chest fluoroscopy were assessed hourly. Results: After 6 hours of ventilation, animals receiving variable ventilation demonstrated significantly higher oxygenation index (PaO2/FiO2 441 ± 37 (mean ± standard deviation) vs. 354 ± 61 mmHg, p<0.001) and lower respiratory elastance (359 ± 36 vs. 463 ± 81 cmH2O/L, p<0.01) than animals receiving pressure-controlled ventilation. Animals ventilated with the variable mode also presented less lung derecruitment (decrease in lung aerated area, –3.4 ± 9.9 vs. –17.9 ± 6.7 %, p<0.01) and intrapulmonary shunt fraction (9.6 ± 4.1 vs. 17.0 ± 5.8 %, p<0.01). Conclusions: Physiologically variable ventilation applied to a model of chronic obstructive pulmonary disease improved oxygenation, respiratory mechanics, lung aeration and intrapulmonary shunt fraction compared to conventional ventilation. A reduction in alveolar derecruitment and lung tissue stress leading to better aeration and gas exchange may explain the benefits of physiologically variable ventilation.